DETERMINATION OF VARIOUS FORM OF IODINE IN HIGH MINERALISED GEOTERMAL WATERS OF CRIMEAN PENINSULA: UDC 546.15:543.24.243 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
In high mineralized geothermal waters was determined the contens of various form of iodine and was obtained isotherms sorption of iodide on chlorid argentum, impregnated on silica gel, and on silica gel with grafted tetraalkylammonium groups, as well as elemental iodine on activated coul.
Keywords: -